From haystack to high precision: advanced sequencing methods to unraveling circulating tumor DNA mutations - Silva, Tamires Ferreira da; Azevedo, Juscelino Carvalho de; Teixeira, Eliel Barbosa; Casseb, Samir Mansour Moraes; Moreira, Fabiano Cordeiro; Assumpção, Paulo Pimentel de; Santos, Sidney Emanuel Batista dos; Calcagno, Danielle Queiroz (Frontiers in Molecular Biosciences, 2024)
Identifying mutations in cancer-associated genes to guide patient treatments is essential for precision medicine. Circulating tumor DNA (ctDNA) offers valuable insights for early cancer detection, treatment assessment, and surveillance. However, a key issue in ctDNA analysis from the bloodstream is the choice of a technique with adequate sensitivity to identify low frequent molecular changes. Nextgeneration sequencing (NGS) technology, evolving from parallel to long-read capabilities, enhances ctDNA mutation analysis. In the present review, we describe different NGS approaches for identifying ctDNA mutation, discussing challenges to standardized methodologies, cost, specificity, clinical context, and bioinformatics expertise for optimal NGS application.